PEMIKIRAN KH. HUSEIN MUHAMMAD TENTANG KONSEP MU’ĀSYARAH BI AL-MA’RŪF DALAM MEMBINA RUMAH TANGGA - Safika, Siti Nurul Aina; Syamsulbahri, Andi; M.Sos, Fajar (IAIN BONE, 2024)
This research examines the concept of mu'Äsyarah bi al-ma'rÅ«f according to KH. Hussein Muhammad. Aims to determine the urgency of the concept of mu'Äsyarah bi al-ma'rÅ«f in building a Muslim family. This research uses a qualitative approach, with secondary data sourced from literature, such as books, books, journals from the figures being researched. Data analysis uses qualitative descriptive methods. The results of this research show that mu'Äsyarah bi al-ma'rÅ«f according to KH. Husein Muhammad is divided into three realms, namely: the economic realm which includes mu'Äsyarah bi al-ma'rÅ«f in marriage (dowry and living), mu'Äsyarah bi al-ma'rÅ«f in sexual relations and mu'Äsyarah bi al-ma 'rÅ«f in human relations. The urgency of implementing mu'Äsyarah bi al-ma'rÅ«f in building a household is a reflection for the generation that will continue family life. So the concept of mu'Äsyarah bi al-ma'rÅ«f is very important to implement, so as to create a quality, loving, humanist and peaceful society.